THE ANALYSIS OF GOVERNMENT EXPENDITURE FOR EDUCATION AND HEALTH SECTOR ON HUMAN DEVELOPMENT INDEX (HDI) IN INDONESIA YEAR 2008-2013 - Beauty, Farlinda Nur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this study is to analyze the influence of government expenditure on education and health sectors in the human development index (HDI) as a measurement of social welfare.This study was quantitative panel data. The data used is time series data (2008-2013 periods) and cross section data (33 province in Indonesia). Type of data uses is secondary data as data which are processed by source of data or related institutions such as Djpk, BPS, Kemenkes, Bkkbn, and Susenas. Method of analysis used in this study is linear regression panel data analysis (pooled data) with Fixed Effect Model as an instrument to process the data by using eviews 7.The finding shows that Education Expenditure has not significant so education expenditure variable will not influence significantly on social welfare, and Health Expenditure has positive relationship and significant influence on social welfare.Keywords: Education Expenditure, Health Expenditure, Social Welfare, and HDI.